PREVALENCE OF CORONARY HEART DISEASE VARIANTS IN MORDOVIA - A. A. Alexandrovskyi; A. A. Usanova; E. V. Kolpakov; V. A. Lusov; L. P. Porunova (Российский кардиологический журнал)
The aim of the study was a comparative assessment of two risk factors (gender and residence) across different variants of acute coronary syndrome (ACS). In 2007-2008, Mordovian doctors participated in the international ACS Registry. The database included 391 patients, hospitalised with ACS diagnosis: 243 from the Saransk City Clinical Hospital No. 4, and 148 from rural central regional hospitals (CRH). The prevalence of different ACS variants was similar in Saransk City men and women. Among rural ACS patients, the percentage of men was higher than the proportion of women. In Saransk City patients with Q wave myocardial infarction (MI), there were more men than women (65,4% vs. 34,6%; p=0,037), while in their peers with stable angina (SA), there were more women than men (28,9% vs. 15,6%; p=0,015). Among urban patients with non-Q wave MI and unstable angina (UA), the proportion of women tended to be higher than that of men. In rural patients with Q wave MI, there were significantly more men than women (66,0% vs. 24,0%; p<0,03). However, no difference in gender distribution was observed for patients with non-Q wave MI, UA, and SA. Multivariate analysis demonstrated that the effects of gender and residence on CHD variants were significant only for ST segment elevation ACS and Q wave MI (2-9%; p<0,01-0,001). For non-ST segment elevation ACS, non-Q wave MI, UA, and SA, the size of these non-significant effects was <1%, or even 0%.